Problems in Physician-Patient Communication: What do our Students See and Hear? A Qualitative Study with a Pragmatic Approach - Younas, Ayesha; Khan, Rehan Ahmed; Yasmeen, Rahila; Mahboob, Usman; Ansar, Ambreen (Annals of King Edward Medical University, 2022)
Background: Efficient communication with patients is an indispensable necessity for physicians of the 21 century. Over the past decades, much work has been done nationally and internationally to instill this essential skill in undergraduate students and medical graduates are now formally trained to become better communicators. However, deficiencies persist and medical students of today still observe various issues when they observe physician- patient communication interactions in their training. Objective: To understand perceptions of undergraduate medical students about the difficulties in Physician-Patient communication (PPC) & take suggestions on how to overcome them. Methods: A qualitative study design was employed, with data collection through three focus group discussions with medical students studying in Wah medical college, Pakistan in October 2019. Thematic data analysis was done using Atlas-ti 8 software. A pragmatic approach was used to understand student perceptions about difficulties in PPC. Conclusion: The various issues regarding the problems in physician patient communication portray a realistic picture of our current communication practices. Various factors have been identified in this study and, the most practical solution to these problems lies in the effective teaching of behavioral sciences.